2017
DOI: 10.1002/ceat.201700070
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Hydrogenation of L‐Arabinose and D‐Galactose in a Mini Packed‐Bed Reactor

Abstract: Dedicated to Professor Rüdiger Lange on the occasion of his 65th birthdayThe continuous hydrogenation of a mixture of L-arabinose and D-galactose over a Ru/C catalyst was investigated in a miniaturized packed-bed reactor. The reaction is one important step of the transformation of the naturally occurring hemicellulose arabinogalactan into valuable sugar alcohols. Process intensification was accomplished by reducing the reactor dimensions to a few millimeters; thus leading to better mass and heat transfer perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 37 publications
(37 reference statements)
1
12
0
3
Order By: Relevance
“…Due to the strong shear force generated by centrifugal forces in the CCCS, liquid-liquid mixing is enhanced considerably, accelerating reactions with fast kinetics that are limited by mass transfer. [134] Typically, microreactors have been used for single liquid phase and biphasic (gas-liquid or liquid-liquid) catalytic transformation of biomass derivatives to valuable products using homogeneous or heterogeneous catalysts (e. g., the (biphasic) synthesis of furans from sugars, [135][136][137][138][139][140][141][142][143][144] (aerobic) oxidation, [144][145][146][147][148][149] and hydrogenation of biomass derivatives [144,[150][151][152][153] ). [126] Another intensified reactor configuration for multiphase (gasliquid or liquid-liquid) catalytic biomass transformation is the spinning disc reactor, consisting of a rotating disc around which fluids are fed.…”
Section: Process Intensification For Biomass Conversionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the strong shear force generated by centrifugal forces in the CCCS, liquid-liquid mixing is enhanced considerably, accelerating reactions with fast kinetics that are limited by mass transfer. [134] Typically, microreactors have been used for single liquid phase and biphasic (gas-liquid or liquid-liquid) catalytic transformation of biomass derivatives to valuable products using homogeneous or heterogeneous catalysts (e. g., the (biphasic) synthesis of furans from sugars, [135][136][137][138][139][140][141][142][143][144] (aerobic) oxidation, [144][145][146][147][148][149] and hydrogenation of biomass derivatives [144,[150][151][152][153] ). [126] Another intensified reactor configuration for multiphase (gasliquid or liquid-liquid) catalytic biomass transformation is the spinning disc reactor, consisting of a rotating disc around which fluids are fed.…”
Section: Process Intensification For Biomass Conversionmentioning
confidence: 99%
“…External (gas-liquid) mass transfer limitations were observed in the slurry reactor, while internal (liquid-solid) mass transfer limitations were more prevalent in the microreactor since the gas-liquid slug flow generated in monolithic channels considerably enhanced the external mass transfer. [151] Both external and internal mass transfer limitations could be diminished by the enhanced gasliquid mass transfer in the microreactor and by using sufficiently small (d p = 80-100 μm) catalyst particles. [150] The hydrogenation of a mixture of C 5 sugars (L-arabinose and D-galactose towards arabitol and galactitol, respectively) was performed in a microreactor (d C = 2.4 mm) packed with 0.5 wt% Ru/C catalysts subject to an upstream slug flow ( Figure 3F; Table 6, entry 2).…”
Section: Hydrogenation Of Sugars To Sugar Alcoholsmentioning
confidence: 99%
“…This rate equation suggests that a surface bimolecular reaction is the rate determining step with an adsorption competition between the sugar and the polyol adsorbed on the active sites of the catalyst. The absence of H 2 term in the denominator of the rate expression is justified according the literature where H 2 is founded to have little influence on the sugars hydrogenation at high pressure (above 30 bar), presenting low adsorption constants [24] or even not being considered in the kinetic model [25] . For example, Sifontes Herrera et al estimated K H2 for the galactose or arabinose hydrogenation at least 100 times lower than the adsorption constants found for sugars and polyols [24] .…”
Section: Resultsmentioning
confidence: 99%
“…Simultaneous hydrogenation of galactose and arabinose was studied by Sifontes Herrera et al [24] . and Müller et al [25] . Both teams observed that arabinose hydrogenation was faster than galactose hydrogenation and estimated similar activation energies for arabinose and galactose; the former team assumed a negligible adsorption of galactose on Ru, whereas the latter team assumed a negligible adsorption of arabinose on Ru.…”
Section: Introductionmentioning
confidence: 99%
“…[22] With Ru/Al2O3 catalyst, at full conversion, higher yields in polyols where obtained from xylose and fructose than for mannose and galactose. [23] Simultaneous hydrogenation of galactose and arabinose was studied by Sifontes Herrera et al [24] and Müller et al [25] Both teams observed that arabinose hydrogenation was faster than galactose hydrogenation and estimated activation energies similar for arabinose and galactose; the former team assumed a negligible adsorption of galactose on Ru, whereas the latter team assumed a negligible adsorption of arabinose on Ru. Simultaneous hydrogenation of xylose, glucose and arabinose over Ru catalysts indicated a slightly slower rate of hydrogenation for glucose but this difference was sometimes negligible depending on the catalytic system.…”
Section: Introductionmentioning
confidence: 99%